2017
DOI: 10.12659/msm.901639
|View full text |Cite
|
Sign up to set email alerts
|

Iliac Vein Compression Syndrome (IVCS): An Under-Recognized Risk Factor for Left-Sided Deep Venous Thrombosis (DVT) in Old Hip Fracture Patients

Abstract: BackgroundThe aim of this study was to identify whether iliac vein compression syndrome (IVCS) is a risk factor for left-sided deep venous thrombosis (DVT) in hip fracture patients and the influence IVCS may have on the treatment of DVT.Material/MethodsA retrospective study was carried out among 424 hip fracture patients admitted to our hospital from 2011 to 2016. Clinical data were analyzed, and all patients were classified into the DVT group and the non-DVT group based on plasmin D-Dimer concentration and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…One-third of DVT patients develop PTS [ 5 ], resulting in significant impact on patient quality of life. Moreover, for populations susceptible to DVT, such as iliac vein compression syndrome (IVCS) in hip fracture patients, more aggressive measures are needed when DVT occurs [ 21 ]. Thus, timely and accurate diagnosis is important to implement active therapy and prevent the deterioration of DVT.…”
Section: Discussionmentioning
confidence: 99%
“…One-third of DVT patients develop PTS [ 5 ], resulting in significant impact on patient quality of life. Moreover, for populations susceptible to DVT, such as iliac vein compression syndrome (IVCS) in hip fracture patients, more aggressive measures are needed when DVT occurs [ 21 ]. Thus, timely and accurate diagnosis is important to implement active therapy and prevent the deterioration of DVT.…”
Section: Discussionmentioning
confidence: 99%
“… 7) Recently, several studies recognized that MTS may be a risk factor for DVT after hip surgery. Liu et al 12) reported that left common iliac vein compression was significantly associated with DVT following hip fracture. Bergen et al 11) showed that left common iliac vein compression significantly increased the risk of DVT following THA.…”
Section: Discussionmentioning
confidence: 99%
“… 11) Recently, several studies suggested that MTS may be a risk factor for DVT after hip surgery. 11 12) However, the exact incidence of MTS among DVT patients who underwent THA is not known.…”
mentioning
confidence: 99%
“…However, unilateral leg swelling and DVT, especially proximal lower extremity, caused by MTS in elderly patients was rarely diagnosed. A retrospective study of elderly patients with hip fractures, mean age of 81 years, showed that 34% of patients who developed DVT had baseline IVCS [ 4 ]. This resulted in an increased risk of DVT of up to 1.5- to two-fold.…”
Section: Discussionmentioning
confidence: 99%